NO LONGER A CONCEPT, BUT A STRATEGIC NECESSITY - Dantsiger, Dmitry Grigorievich; Filimonov, Sergey Nikolaevich; Chasovnikov, Konstantin Viktorovich; Kozhevnikov, Andrey Aleksandrovich (Medicine in Kuzbass, 2026)
Without minimizing the achievements of recent years in academic medical science, we must recognize the growing problems in health protection and the availability of medical care. Unfortunately, the stagnation of the system concerns both primary and specialized links. Attempting to link these intractable problems solely to government funding for the industry is misguided.